Fertilitätserhalt bei onkologischen Patientinnen - Horn, Kyra von (Der Onkologe, 2017)
Due to the continuous optimization of chemotherapy and radiotherapy, there has been a significant increase in the survival of patients with malignant disease. Oncological treatment can cause permanent damage to ovarian and testicular tissue. This represents an additional stress factor for patients and their partners. It is therefore of paramount importance to offer timely counselling on options for fertility preservation. Cryopreservation of spermatozoa and testicular tissue, cryopreservation of ovarian tissue, fertilized and unfertilized oocytes and ovarian transposition in the case of pelvic radiation are established therapeutic options. Hormone therapy in women is still the subject of controversy. The German network FertiPROTEKT was founded in 2006 with the aim of bringing oncologists’ and reproduction specialists’ expertise together, developing extensive infrastructure and carrying out scientific data collection.